Timing of percutaneous vertebroplasty in the management of osteoporotic vertebral compression fractures: a retrospective cohort study - Wei, Huawei; Zhang, Qiuxue; Song, Bing; Yue, Hongwei; Li, Jing; Zhang, Hongjian; Wang, Yanming (Frontiers in Surgery, 2025)
IntroductionOsteoporotic vertebral compression fractures (OVCFs) are common in older populations, and cause pain and kyphosis, impacting patient quality of life. This study aimed to determine the optimal timing of percutaneous vertebroplasty (PVP) for the treatment of OVCFs.MethodsThis retrospective cohort study included 120 older patients with OVCFs admitted to our hospital between January 2020 and December 2022. Patients were divided into three groups according to the timing of PVP surgery: Group A, within 7 days of the OVCF; Group B, 8–14 days after the OVCF; and Group C, 15–28 days after the OVCF. Preoperative and postoperative visual analog scale scores, the Oswestry Disability Index, vertebral height, Cobb angle, and complications were compared among the three groups.ResultsPVP surgery within 7 days of the OVCF led to rapid pain relief and restoration of vertebral function; preoperative visual analog scale scores and the Oswestry Disability Index were significantly higher in this group compared with the other two groups, but no significant differences among the three groups were observed postoperatively. However, early surgery was also associated with a higher rate of bone cement leakage compared with the other two groups, whereas delayed PVP was associated with a greater incidence of deep vein thrombosis and urinary infections.DiscussionThe timing of PVP surgery in the management of OVCFs impacts patient outcomes. Early surgical treatment may result in greater pain relief, improved vertebral function, and fewer complications, but patient-specific factors should be considered when determining the optimal surgical timing.